Quantifying the thermal mitigation effects of urban parks under different irrigation scenarios and tree-densities using ENVI-met and field measurements - Tommaso Giordano; Fabio Castelli; Giandomenico de Luca; Donatella Fibbi; Beniamino Gioli; Giovanni Gualtieri; Jannik Heusinger; Marianna Nardino; Simone Putzolu; Stephan Weber; Alessandro Zaldei; Lorenzo Brilli (Sustainable Cities and Society, 2026)

Anthropogenic heat flux from air-conditioning: direct measurements and meteorological controls - Milena Heyen; Jannik Heusinger; Stephan Weber (Urban Climate, 2026)

Combining shortwave reflectivity and evaporation in a novel rooftop solution for urban cooling - Linus Faymonville; Jannik Heusinger; Stephan Weber (Urban Climate, 2026)

Historical Demography and Patterns of Connectivity Among Three Groups of Mandrills (Mandrillus sphinx) in Lopé National Park, Gabon - Anna Weber; Amour Guibinga Mickala; David Lehmann; Stephan Ntie; Katharine Abernethy; Patrick Mickala; Nicola Anthony (International Journal of Primatology, 2026)

Carbon and water exchange in extensive green roofs: A comparison between eddy covariance and soil flux chamber observations - Patrick Hansen; Jannik Heusinger; Stephan Weber (Urban Forestry & Urban Greening, 2025)

Integrated monitoring of road traffic and airborne ultrafine particles at a camera-equipped urban intersection - Tobias Schripp; Kay Gimm; Tobias Grein; Clemens Schicktanz; Stephan Weber; Markus Köhler (Atmospheric Pollution Research, 2025)

Changes in soil mechanical and hydraulic properties through regenerative cultivation measures in long-term and farm experiments in Germany - Carolina Bilibio; Tobias Karl David Weber; Markus Hammer-Weis; Stephan Martin Junge; Simeon Leisch-Waskoenig; Janos Wack; Wiebke Niether; Andreas Gattinger; Maria Renate Finckh; Stephan Peth (Soil and Tillage Research, 2025)

Prediction of urban ultrafine particle emission fluxes using generalized additive models - Tobias Bitz; Lars Gerling; Fred Meier; Stephan Weber (Atmospheric Environment, 2024)

Water storage levels and water storage capacity of an extensive green roof quantified from multi-year eddy covariance measurements - Niklas Markolf; Jannik Heusinger; Stephan Weber (Ecological Engineering, 2024)

Predicting multi-annual green roof net ecosystem exchange using machine learning - Timothy Husting; Boris Schröder; Stephan Weber (Building and Environment, 2024)

What mandrills leave behind: using fecal samples to characterize the major histocompatibility complex in a threatened primate - Anna Weber; Jackie Lighten; Cock van Oosterhout; Amour Guibinga Mickala; Stephan Ntie; Patrick Mickala; David Lehmann; Katharine Abernethy; Nicola Anthony (Conservation Genetics, 2024)

Modeling the impacts of building energy efficiency on the thermal microclimate in a midsize German city - Jannik Heusinger; Nils Bruchmann; Stephan Weber (Urban Climate, 2023)

hyd1d and hydflood - R packages to compute water levels and annual flood durations along the rivers Rhine and Elbe, Germany - Arnd Weber; Marcus Hatz; Wiebke Schramm; Stephan Rosenzweig (Ecohydrology & Hydrobiology, 2023)

Mobile measurements of atmospheric pollutant concentrations in the pollutant plume of BER airport - Lars Gerling; Stephan Weber (Atmospheric Environment, 2023)

A mid-infrared study of synthetic glass and crystal mixtures analog to the geochemical terranes on mercury - Andreas Morlok; Christian Renggli; Bernard Charlier; Olivier Namur; Stephan Klemme; Maximilian P. Reitze; Iris Weber; Aleksandra N. Stojic; Karin E. Bauch; Harald Hiesinger; Joern Helbert (Icarus, 2023)

Estimation of the census (Nc) and effective (Ne) population size of a wild mandrill (Mandrillus sphinx) horde in the Lopé National Park, Gabon using a non-invasive genetic approach - Amour GuibingaMickala; Anna Weber; Stephan Ntie; Prakhar Gahlot; David Lehmann; Patrick Mickala; Katherine Abernethy; Nicola Anthony (Conservation Genetics, 2022)

Competition for light induces metal accumulation in a metal hyperaccumulating plant - Anubhav Mohiley; Katja Tielbörger; Michael Weber; Stephan Clemens; Michal Gruntman (Oecologia, 2021)

Importance of oxidation products in coumarin-mediated Fe(hydr)oxide mineral dissolution - Matthias Baune; Kyounglim Kang; Walter D. C. Schenkeveld; Stephan M. Kraemer; Heiko Hayen; Günther Weber (BioMetals, 2020)

Distance measurements in the F0F1-ATP synthase from E. coli using smFRET and PELDOR spectroscopy - Markus Burger; Stephan Rein; Stefan Weber; Peter Gräber; Sylwia Kacprzak (European Biophysics Journal, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Governing complexity: How can the interplay of multilateral environmental agreements be harnessed for effective international market-based climate policy instruments? - Stephan Hoch; Axel Michaelowa; Aglaja Espelage; Anne-Kathrin Weber (International Environmental Agreements: Politics, Law and Economics, 2019)

The HLA ‐B landscape of Africa: Signatures of pathogen‐driven selection and molecular identification of candidate alleles to malaria protection - Alicia Sanchez‐Mazas; Viktor Černý; Da Di; Stéphane Buhler; Eliška Podgorná; Elodie Chevallier; Lydie Brunet; Stephan Weber; Barbara Kervaire; Manuela Testi; Marco Andreani; Jean‐Marie Tiercy; et al. (Molecular Ecology, 2017)
Human leukocyte antigen ( HLA ) genes play a key role in the immune response to infectious diseases, some of which are highly prevalent in specific environments, like malaria in sub‐Saharan Africa. Former case–control studies showed that one particular HLA ‐B allele, B*53, was associated with malaria protection in Gambia, but this hypothesis was not tested so far within a population genetics framework. In this study, our objective was to assess whether pathogen‐driven selection associated with malaria contributed to shape the HLA ‐B genetic landscape of Africa. To that aim, we first typed the HLA ‐A and ‐B loci in 484 individuals from 11 populations living in different environments across the Sahel, and we analysed these data together with those available for 29 other populations using several approaches including linear modelling on various genetic, geographic and environmental parameters. In addition to relevant signatures of populations’ demography and migrations history in the genetic differentiation patterns of both HLA ‐A and ‐B loci, we found that the frequencies of three HLA alleles, B*53, B*78 and A*74, were significantly associated with Plasmodium falciparum malaria prevalence, suggesting their increase through pathogen‐driven selection in malaria‐endemic environments. The two HLA ‐B alleles were further identified, by high‐throughput sequencing, as B*53:01:01 (in putative linkage disequilibrium with one HLA ‐C allele, C*04:01:01:01) and B*78:01 in all but one individuals tested, making them appropriate candidates to malaria protection. These results highlight the role of environmental factors in the evolution of the HLA polymorphism and open key perspectives for functional studies focusing on HLA peptide‐binding properties.

Suppression of PPARβ, and DHA treatment, inhibit NaV1.5 and NHE-1 pro-invasive activities - Ramez Wannous; Emeline Bon; Ludovic Gillet; Julie Chamouton; Günther Weber; Lucie Brisson; Jacques Goré; Philippe Bougnoux; Pierre Besson; Sébastien Roger; Stephan Chevalier (Pflügers Archiv - European Journal of Physiology, 2015)

Complete genome of a Puumala virus strain from Central Europe - Hanan Sheikh Ali; Stephan Drewes; Vanessa Weber de Melo; Mathias Schlegel; Jona Freise; Martin H. Groschup; Gerald Heckel; Rainer G. Ulrich (Virus Genes, 2015)

Diabetes and atrial fibrillation: stratification and prevention of stroke risks - Stephan v Bandemer; Sebastian Merkel; Anna Nimako-Doffour; Mattias M Weber (EPMA Journal, 2014)

Risk detection and risk management for diabetes patients with atrial fibrilation - Matthias M Weber; Stephan von Bandemer (EPMA Journal, 2014)

Comparison of atmospheric turbulence characteristics and turbulent fluxes from two urban sites in Essen, Germany - Stephan Weber; Klaus Kordowski (Theoretical and Applied Climatology, 2010)

Urban/rural atmospheric water vapour pressure differences and urban moisture excess in Krefeld, Germany - Wilhelm Kuttler; Stephan Weber; Judith Schonnefeld; Alexandra Hesselschwerdt (International Journal of Climatology, 2007)
Urban/rural humidity differences were analysed by means of a climate station pair in Krefeld (51° 20′N, 6° 33′E), Germany, during the period from 11/2001 to 10/2002, on the basis of hourly averages of water vapour pressure. Focus was put upon on the examination of frequency, timing and duration of the Urban Moisture Excess (UME) (Δ e u−r > 0 hPa). It was found that the urban site was more humid (0 hPa e u−r ⩽0.5 hPa; weak UME) in 31.4% of the cases investigated and was only rarely significantly more humid (Δ e u−r > 0.5 hPa; intense UME) in 4.6%. Weak and intense UME occur during every month of the year with different frequencies per month. A diurnal course of UME was found for summer but not for winter. Weak and intense UME events show frequency maxima in the second half of the night. Most of them are characterized by durations of 1 hour, in few cases several hours duration were observed for weak (up to 14 h) and intense UME (up to 12 h). The main reason for formation of UME events might be that the surface dew point at the rural station was reached more often, earlier and lasted longer in comparison to the urban environment. Copyright © 2007 Royal Meteorological Society